2022
DOI: 10.1021/acs.joc.1c03157
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Asymmetric [3 + 2] Annulation of Vinylethylene Carbonates with Alkenes Installed on Cyclic N-Sulfonyl Imines: Highly Enantio- and Diastereoselective Construction of Chiral Tetrahydrofuran Scaffolds Bearing Three Vicinal and Quaternary Stereocenters

Abstract: A multisubstituted tetrahydrofuran building block bearing three vicinal chiral carbon centers widely exists in a broad spectrum of bioactive natural products, and the development of efficient and convenient methods to establish this skeleton remains a challenging task. Herein, we have developed an efficient method for the construction of significant tetrahydrofuran scaffolds bearing three vicinal and α-quaternary chiral carbon stereocenters through Pd-catalyzed asymmetric [3 + 2] annulation of vinylethylene ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Recently, the group of Chen and Lan found that the [3+2] annulations could also be achieved using cyclic N -sulfonyl imines 218 as dipolarophiles, which provided a direct entry to chiral tetrahydrofuran scaffolds bearing three vicinal and quaternary stereocenters (Scheme 47). 104 DFT calculations revealed that the enantio-determining step of this transformation was the annulation process, and methanol was involved in stabilizing the reactive zwitterionic π-allylpalladium via H-bond interactions.…”
Section: Cyclization Involving π-Allyl Palladium Zwitterionsmentioning
confidence: 99%
“…Recently, the group of Chen and Lan found that the [3+2] annulations could also be achieved using cyclic N -sulfonyl imines 218 as dipolarophiles, which provided a direct entry to chiral tetrahydrofuran scaffolds bearing three vicinal and quaternary stereocenters (Scheme 47). 104 DFT calculations revealed that the enantio-determining step of this transformation was the annulation process, and methanol was involved in stabilizing the reactive zwitterionic π-allylpalladium via H-bond interactions.…”
Section: Cyclization Involving π-Allyl Palladium Zwitterionsmentioning
confidence: 99%
“…Chiral aldehyde catalysis has been proven to be a brilliant approach for the asymmetric α-functionalization of NH 2 -unprotected amino acid esters. [3][4][5] It is vital that the α-functionalized products have free amino groups that can participate as nucleophilic sites in subsequent cascade reactions to construct optically active nitrogen heterocyclic molecules (Scheme 1). In 2018, we disclosed the first chiral aldehyde catalyzed cascade reaction of glycinate, in which the conjugate addition and condensation occurred successively, resulting in optically active Δ(1)-pyrrolines (Scheme 1, eqn (1)).…”
Section: Introductionmentioning
confidence: 99%
“…We were inspired by the fact that vinylethylene carbonates were not only applied in cycloaddition but also employed in nucleophilic substitution. 11–16 To the best of our knowledge, methods by attacking the terminal position of intermediate C for the construction of chiral functionalized products with the ( Z )-configuration are still scarce and underdeveloped. 17 A single catalytic style mode was difficult to control the chiral stereo center owing to the long distance of the prochiral center with the π-allylpalladium intermediate.…”
mentioning
confidence: 99%